Набуття прав на акції товариства - Костова, Наталія Іванівна; Костова, Наталия Ивановна; Kostova, Natalia I. (My University, 2015)
Стаття присвячена дослідженню надання акціонерам переважного права на придбання акцій, що є однією із ключових ознак, яка відрізняє приватне акціонерне товариство від публічного, що передбачає встановлення переважного права на придбання акцій акціонерами.

Статья посвящена исследованию предоставления акционерам преимущественного права на приобретение акций – одним из ключевых признаков, отличающих частное акционерное общество от публичного, что предусматривает установление преимущественного права на приобретение акций акционерами.

The article is devoted to a study of the shareholders pre-emptive right to acquire shares – one of the key features that distinguishes private from public joint stock company provides for the establishment of pre-emptive right to acquire shares by shareholders. The fact that the law of the private joint-stock company, the charter of a society violates the principle of equality before the law. In fact, in certain situations the law gives the right owners and large controlling stakes, taking Articles of Association, will limit their ownership of other shareholders for their shares by maintaining their pre-emptive right to purchase them.
Костова Н. І. Набуття прав на акції товариства / Н. І. Костова // Часопис цивілістики. – 2015. – Вип. 19. – С. 65-68.
Keywords: поняття акції; набуття прав на акції товариства; публічне акціонерне товариство; засновники товариства; підстави припинення участі засновника у заснуванні товариства; понятие акции; приобретение прав на акции общества; публичное акционерное общество; учредители общества; основания прекращения участия учредителя в создании общества; concept stocks; acquisition of rights to shares of the company; a public joint stock company; the founders of the company; the grounds for termination of participation in the establishment of the company founder